Meeting the challenges of implementing rapid genomic testing in acute pediatric care - Stephanie Best (GENETICS in MEDICINE, 2018)
Authors: Stark, Z. Lunke, S. Brett, G. Tan, N. Stapleton, R. Kumble, S. Yeung, A. Phelan, D. Chong, B. Fernandez, M.F. Marum, J.E. Hunter, M. Jarmolowicz, A. Yael Prawer, Y. Riseley, J.R. Regan, M. Elliott, J. Melissa Martyn, M. Best, S. Tan, T. Clara L Gaff, C.L. and White, S.M.